Assessing soil characteristic under reforestation of indulgenous tree species: A case study at Sampadi forest reserve, Lundu - Christina, Leysia (Universiti Malaysia Sarawak (UNIMAS), 2012)
Vast area of tropical rainforests is degraded by human activities every year. The degraded lands are left as low productivity and low biodiversity. In Sarawak, the forests is decreasing due to land use conversions required for other developments such as agriculture, clearing for commercial, housing and industrial purposes. The remaining forest stands, even at the remote areas and lack of accessibility due to mountainous geological formation are also under increasing pressure from the logging activity. Reforestation activities have been launched to convert the degraded area into productive forests. This study is conducted to clarify the soil under reforestation area and to determine whether the soil is suitable for the growth of the dipterocarp species, Shorea macrophylla in Sampadi Forest Reserve, Lundu) The soil profile of the study area was examined in-situ from a soil pit that was dug with the size of lOx 10m2 at the reforestation area planted with Shorea macrophylla in year 1996. A vertical section of the soil from the surface through all its horizons was observed to verify the soil profile. The soil profile composed of p, A, B\, B2 and B3 horizon. The status of soil under reforestation clarified in this study. Laboratory results for the soils indicated that the soil pH at the study area to be acidic and the readings were increased with the '\ increasing depth. The soil organic matter in the upper horizon was indicated to be higher and this contributes to the higher organic nutrient at the A horizon, consequently improved the fertility status of the soil. The values of bulk density at the study site were ranging from 1.15 g cm- I to 1.64 g cm-I . On the other hand, the soil hardness of all identified horizons was measured ranging from 17mm to 22mm. It was .' indicated that the soil hardness increased with the increasing of depth. From this study, it was revealed that rehabilitating using Shorea macrophylla definitely offers a potential to improve site productivity.